Herramientas de Marketing digital y competencia: una aproximación al estado de la cuestión; Digital marketing tools and competition: an approach to the state of the art - Matías Membiela-Pollán; Natalia Pedreira-Fernández (Atlantic Review of Economics (ARoEc), 2019)
– In recent years, the rise of ICT has resulted in the dimension that digital marketing currently has, understood as the use of technological resources in the development of the market strategy, as well as in the commercialization and communication of the organization. This article aims to carry out a review of the state of the art in regards to the concept, evolution and techniques of digital marketing. Specifically, the text extends to the understanding of seven tools: the corporate website and online store, blogs, social networks, e-mail marketing, SEO, SEM, and digital advertising. Its proper use reverts to greater efficiency in responding to market needs; and serves to increase the number of transactions and the brand equity, implying all this an improvement of the business result.
Keywords: 330; Marketing; digital marketing; E-commerce; social media; digital advertising; SEO; SEM